The influence of customer perceived value and service quality on customer loyalty through customer satisfaction: A case study report - Dewanti Putri Nurita; Vip Paramarta; Kosasih Kosasih; Farida Yuliaty; Etty Sofia Mariati Asnar (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Preliminary findings indicate a patient loyalty issue at XYZ Hospital, Tangerang. Purpose: To analyze the partial effect of Customer Perceived Value and Service Quality on Customer Loyalty, both directly and indirectly through the mediation of Customer Satisfaction. Method: A quantitative approach with an asymmetric causal design was employed. This study employed descriptive and verification methods and adopted a survey-based approach. The study was conducted at XYZ Hospital, Tangerang, Banten, in 2025. The population included all hospital outpatients, with a sample size of 123 respondents. Data were collected through a survey and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Results: This study indicates that customer perceived value significantly influences customer satisfaction and loyalty. Service quality also has a positive and significant impact on customer satisfaction and loyalty. Furthermore, customer satisfaction has a significant positive effect on customer loyalty. Furthermore, customer satisfaction mediates the relationship between service quality and customer loyalty. However, it does not mediate the relationship between customer perceived value and customer loyalty. Conclusion: increasing service quality and customer perceived value can increase satisfaction and loyalty, with satisfaction acting as a mediator, particularly in the relationship between service quality and customer loyalty.